006. Wilm’s Tumor with Obstructive Ileus in A Newborn - Soebagio, Sanjaya; Jaya, I Made Darma (JBN (Jurnal Bedah Nasional), 2024)
Background : Wilms' tumor is the most common kidney malignancy in the pediatric population. Wilms' tumor can spread to other organs, pressing on surrounding organs, and causing kidney damage and high blood pressure. This case report aims to report on neonatal patients with Wilms' tumor which complicate into obstructive ileus. This study aims to explore the effect of wilm’s tumor on causing obstructive ileus which can be detrimental to a newborn. Methods : A 21-day-old baby boy was brought in with complaints of a lump in the left abdomen that had been felt since birth. The lump was felt to be growing rapidly and feels hard. Physical examination revealed sunken eyes, dry lips, holosystolic murmur on parasternal line intercostal II-IV, and a solid mass sized 5x4 cm in the left hypochondrium up to left iliac region. Abdominal ultrasound and CT scan confirmed a renal mass. Results : The patient was diagnosed with partial obstructive ileus due to left kidney tumor suppression, suspected Wilms tumor and low intake malnutrition with moderate to severe dehydration. The patient was managed with laparotomy and left nephrectomy. The procedure alleviated all symptoms and upon 1 month follow up, the patient was healthy with good nutrition status. Conclusion: The presence of large abdominal mass in neonates can be a sign of Wilms tumor. This disease can lead to obstructive ileus and can be treated with laparotomy and nephrectomy.